Bottom–Up Evolution of Diamond–Graphite Hybrid Two‐Dimensional Nanostructure: Underlying Picture and Electrochemical Activity. Issue 8 (11th December 2021) - Cho, Jung‐Min; Ko, Young‐Jin; Lee, Hak‐Joo; Choi, Heon‐Jin; Baik, Young‐Joon; Park, Jong‐Keuk; Kwak, Joon Young; Kim, Jaewook; Park, Jongkil; Jeong, YeonJoo; Kim, Inho; Lee, Kyeong‐Seok; et al.
Abstract: The diamond–graphite hybrid thin film with low‐dimensional nanostructure (e.g., nitrogen‐included ultrananocrystalline diamond (N‐UNCD) or the alike), has been employed in many impactful breakthrough applications. However, the detailed picture behind the bottom–up evolution of such intriguing carbon nanostructure is far from clarified yet. Here, the authors clarify it, through the concerted efforts of microscopic, physical, and electrochemical analyses for a series of samples synthesized by hot‐filament chemical vapor deposition using methane–hydrogen precursor gas, based on the hydrogen‐dependent surface reconstruction of nanodiamond and on the substrate‐temperature‐dependent variation of the growth species (atomic hydrogen and methyl radical) concentration near substrate. The clarified picture provides insights for a drastic enhancement in the electrochemical activities of the hybrid thin film, concerning the detection of important biomolecule, that is, ascorbic acid, uric acid, and dopamine: their limits of detections are 490, 35, and 25 nm, respectively, which are among the best of the all‐carbon thin film electrodes in the literature. This work also enables a simple and effective way of strongly enhancing AA detection. Abstract : The authors clarify the nucleation/growth mechanism of diamond–graphite hybrid thin film with 2D nanostructure (the only successful diamond probe material for neural recording/stimulation), based on nanodiamond surface reconstruction controlled by growth species variation in growth environment. It provides insights for the drastic enhancement of the structure‐optimized thin film performance in simultaneous electrochemical detection of dopamine, ascorbic acid, and uric acid.